Implikasi Kontrol Diri, Kecerdasan Spiritual dan Literasi Keuangan dalam Pengelolaan Keuangan - Nurjanah, Rina; Asti, Eka Giovana; Rafikah, Ismi; Istiqomah, Anisah (Owner : Riset dan Jurnal Akuntansi, 2024)
Financial management is the process of planning, organising, supervising, and controlling the money or financial assets of a person or organisation. The goal is to manage finances wisely by maximising the use of financial resources to meet daily needs, achieve short-term and long-term financial goals, and manage financial risks. This includes budgeting, saving, investing, debt management, retirement planning, and other financial decisions. Good financial management is the key to achieving financial stability and achieving financial goals. Students carrying out financial management are influenced by several factors including internal factors such as self-control, and spiritual intelligence. Then external factors, namely knowledge or the level of financial literacy possessed by students. This study aims to analyse the effect of self-control, spiritual intelligence, and financial literacy on individual financial management. Good financial management is the key to success in achieving personal financial stability and long-term financial goals. The research population was Pelita Bangsa University students with a sample of Faculty of Economics and Business students. The results showed that self-control has no effect on one's financial management. Meanwhile, financial literacy and spiritual intelligence have a significant positive effect on financial management. The results prove that when someone has high financial literacy coupled with spiritual intelligence, the ability to manage finances will be better. However, self-control is not indicated to influence a person to carry out financial management. Simultaneously, it shows that self-control, spiritual intelligence and financial literacy together affect financial management. The results of the study have a strong relationship of 76